PSI-2 Weight change affects mineral excretion and markers of bone turnover in horses. (7th December 2018) - Fowler, A; Pyles, M; Hayes, S; Crum, A; Bill, V; Harris, P; Krotky, A; Lawrence, L
Abstract: Many overweight horses are fed less DE than maintenance in an attempt to reduce fat deposits. However, little is known about the effects of weight change on the equine skeleton. The current study aimed to examine the short term effects of feeding diets varying in DE, but similar in mineral content, on bone metabolism and mineral excretion. Fifteen mature horses were assigned to three treatments: weight loss (LO), weight maintenance (MA) and weight gain (GA). Diets were formulated to be 75%, 100%, and 145% of maintenance DE for each of the three treatments, respectively, but similar in crude protein and minerals. Horses were fed diets for 3 to 5 wks and then a total fecal collection was performed to evaluate mineral excretion. Blood samples were taken before and after each dietary period to examine markers of bone metabolism. Bodyweight was monitored daily. Data were analyzed using repeated measures ANOVA with treatment as the main effect and day of collection as the repeated random effect. Horses fed the GA diet had the smallest weight change of +6.25 kg, whereas horses fed both the MA and LO diets lost similar amounts of weight (-9.35 kg and -11.05 kg, respectively). After being fed the LO and MA diets horses had lower serum concentrations of BAP, a marker of bone formation, than horses fed GA (P < 0.05). A marker of bone resorption (CTX-1) was greater after feeding the LO than the GA diet (P < 0.05). Collectively, the bone markers suggested that weight gain and loss affected bone turnover. Horses in the GA group had the lowest fecal P excretion (29.62 mg P/kg BW) and LO horses had the greatest (32.9 mg P/kg BW; P = 0.0853), potentially related to changes in bone turnover. Fecal Ca excretion was not different between treatments.